The LGBT's Propaganda: A Content Analysis of News on the GAYa Nusantara and NU Online - Achmad Zuhri; Laela Fitriyatul Khoeriyah; Nida Nur Hanifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Indonesia is a state of law, but so far there is no legislation or government regulations that strictly regulate the existence of Lesbians, Gays, Bisexuals, and Transgender (LGBT). So there are often both pros and cons to its existence in the midst of society. At the same time, pro-LGBT groups conduct propaganda, one of which is GAYa Nusantara. Meanwhile, groups opposed to LGBT, such as Nahdlatul Ulama' continue to reject the propaganda through NU Online. This research aims to analyze the specific missions of the two websites. To conduct the research, this article uses agenda-setting theory, literature study, and interview approaches. The data collected is analyzed using news content analysis techniques, namely text, context, and social discourse analysis. This article argues that it is important to understand a news text as the result of an editorial room that has a certain mission in conveying public information. The mission carries the ideology of the GAYa Nusantara and NU Online media. The GAYa Nusantara portal has a mission to fight for LGBT equality and welfare, and the NU Online portal has a mission to reject LGBT behavior but does not hate LGBT people.